RENCANA PENAMBANGAN BATUBARA TRIWULAN PADA CV. KUTAI KUMALA ENERGY KECAMATAN LOA KULU, KABUPATEN KUTAI KARTANEGARA, PROVINSI KALIMANTAN TIMUR : QUARTERLY COAL MINING PLAN AT CV. KUTAI KUMALA ENERGY LOA KULU DISTRICT, KUTAI KARTANEGARA REGENCY, EAST KALIMAN - Zwageri, Rizky; Devy, Shalaho Dina; Nugroho, Windhu; Winarno, Agus; Magdalena, Henny (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2022)
Mining design is part of the planning stages of mining as a very important factor is determined before the actual mining plan begins. CV. Kutai Kumala Energy is a company engaged in coal mining which has a Mining Business License located in Loa Kulu District, Kutai Kartanegara Regency, East Kalimantan Province. On CV. Kutai Kumala Energy pit BC was calculated with the aim of meeting the overburden of 5,095,565.38 BCM and the coal stripping target of 673,541.31 MT. In determining production targets for 1 year and in accordance with the capabilities of the tools at the research location.